Mathemathics education: strengthening the Islamic belief - Noormaizatul Akmar Ishak; Maz Jamilah Masnan; Noor Asliza Abdul Rahim; Siti Aisyah Mohd Nor (Universiti Teknologi Malaysia (UTM), 2008)
Organized by Universiti Teknologi Malaysia (UTM), 18th - 19th March 2008 at Putra World Trade Centre, Kuala Lumpur.